Effect of aerial application of adjuvants on pepper defoliant droplet deposition and efficacy of defoliation sprayed by unmanned aerial vehicles - Liu, Yapeng; Xiao, Qinggang; Han, Xiaoqiang; Zeeshan, Muhammad; Fang, Zhihao; Dou, Zechen (Frontiers in Plant Science, 2022)
Defoliant spraying is an important aspect of mechanized processing pepper harvesting. Fully and uniformly spraying defoliant could improve the quality of defoliation and reduce the impurity content in processing pepper. In this study, we assessed the effect of aviation spray adjuvants on physicochemical properties of defoliant solution and droplet deposition, defoliation sprayed by an unmanned aerial vehicle (UAV). The results showed that Puliwang was screened out as the better aviation spray adjuvant suitable for spraying defoliant of processing pepper by UAV, with a higher defoliation rate and better effect to improve droplet deposition. Although the droplets added with YS-20 adjuvant had higher deposition amount (0.72 μg/cm2) in the middle layer, its performance was poor in droplet size, density and coverage. The size and density of the droplets added with the Manniu were basically the same as the Puliwang, even the distribution uniformity was better (the CV of the upper canopy layer was only 33.6%), but the coverage rate was poor. In the treatment with AS-901N, there was no marked increase in droplet size, so evaporation and drift were not improved, eventually resulting in a lower defoliation rate. Puliwang had the highest comprehensive score, followed by AS-910N, YS-20 and Manniu.